2004
DOI: 10.1590/s1679-87592004000200006
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticides residues and PCBs in benthic organisms of the inner shelf of the São Sebastião Channel, São Paulo, Brazil

Abstract: Thirty seven benthic samples of the inner shelf area of São Sebastião, Brazil, were collected between April 1994 and August 1998 and analysed for seventeen chlorinated pesticide residues and PCBs congeners. Pesticide residues and PCBs congeners levels were low (ng/g) and predominantly found in the crustacean samples. DDE was the most frequently residue with a maximum of 9,7 ng/g followed by HCHs with maximum of 17,1ng/g. As for the PCBs, the heavier congeners predominate: CB 138,153,170, 180 and 183. Maximum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
(22 reference statements)
1
6
0
1
Order By: Relevance
“…Thus, the eggs may be viewed as a unique form of excretion of these contaminants from the crab's body. Other available study with benthic organisms (decapod crustaceans) along the Sao Paulo coastal area, showed that the total PCB and DDT levels were lower than 20 ppb (dry weight), one order of magnitude lower than the present results (Gorni & Weber, 2004). These results agree with that found by There seems to have no direct correspondence between soil concentration and egg concentration of organochlorines in the study area ( Figure 5), especially for PCBs.…”
Section: Granulata Density and Organochlorine Concentrationssupporting
confidence: 87%
“…Thus, the eggs may be viewed as a unique form of excretion of these contaminants from the crab's body. Other available study with benthic organisms (decapod crustaceans) along the Sao Paulo coastal area, showed that the total PCB and DDT levels were lower than 20 ppb (dry weight), one order of magnitude lower than the present results (Gorni & Weber, 2004). These results agree with that found by There seems to have no direct correspondence between soil concentration and egg concentration of organochlorines in the study area ( Figure 5), especially for PCBs.…”
Section: Granulata Density and Organochlorine Concentrationssupporting
confidence: 87%
“…PCB profiles of scallops were similar to the profile of other bivalve or cephalopod mollusks, crustaceans, such as mussel, cockle, clam, octopus, crabs collected in other marine or estuarine systems (Carro and others 2004; Gorni and Weber 2004; Storelli and others 2006; Denton and others 2006). The PCB profile was dominated by the higher chlorinated congeners, the lower chlorinated congeners were present in very low concentrations.…”
Section: Resultsmentioning
confidence: 58%
“…Kihara & Rocha, 1993-Callinectes danae Smith, 1869Lacerda, 1981Mossolin, 1994;Caprara & Freitas, 1996;Lowenthal et al 1996;Nucci, 1998;Genofre et al 2000;Nucci et al 2001;Turra & Leite, 2005;Padovanni, 2009-Callinectes ornatus Ordway, 1863Nucci, 1998Nucci et al 2001;Gorni & Weber, 2004-Clibanarius antillensis Stimpson, 1862Garcia, 1979Brossi-Garcia & Hebling, 1983;Arantes & Leite, 1991bJacobi, 1992;Leite et al 1995Leite et al , 1996Nalesso et al 1995;, 20022004Turra et al , 1999Turra et al , 2000Barata et al 1996;Castelo-Branco et al 1996;Jacobucci & Leite, 1996;Turra & Denadai, 2001, 2002, 2004Souza, 2003;Turra, 2003Turra, , 2004Turra, , 2005 Clibanarius sclopetarius (Herbst,1796) Brossi- Garcia, 1987;Arantes & Leite, 1991bJacobi, 1992;Leite et al 1995...…”
Section: Táxon Superior Espéciementioning
confidence: 99%